Rancang Bangun Aplikasi Penjualan Perlengkapan Olahraga (Studi Toko Baratha Sports) - Sinta Rukiastiandari; Yohanes Ulu Mado (JURNAL TEKNIK KOMPUTER, 2019)
The Baratha Sports store is a store that serves various types of sales of sports equipment such as socks, soccer shoes, soccer clothes and other things. In 2013, this shop was founded by Mr. Tohir Adnan, located on Jalan Kinibalu Raya No.19 Harapan Jaya, Bekasi Utara. During this time the process of recording sales, processing the data of sporting goods and sales transaction data is still done using handwriting and still using book media. Difficulties in the process of recording sales and calculating the number of types and quantities of goods resulted in the data obtained being less accurate. To improve the accuracy of the data, it is necessary to develop a computerized sales information system.In this writing the author will present a site on the internet that deals with the sale of sports equipment, which aims to convey information on the sale of sports equipment online, making it easier for consumers to purchase products from the Baratha Sports Shop. In this research phase the making of program code the author uses supporting software such as Xampp, Programming Language PHP, HTML, Jquery and CSS and databases using MySQL. and the method used using the Waterfall method. Mozilla Firefox as a browser, Microsoft paint for editing images.This application is expected to help users (users) in the transaction process ordering equipment and sports equipment, facilitate the checking of the amount of equipment available sports equipment and facilitate the company in disseminating information and product promotion.